Interleukin-10 protects neonatal mice from lethal group B streptococcal infection. - Cusumano, V (1996)
We investigated the role of interleukin-10 (IL-10) in a neonatal mouse model of lethal group B streptococci (GBS) sepsis. Plasma IL-10 levels significantly increased at 24 and 48 h after GBS inoculation. Neutralization of IL-10 with specific antibodies had no effect on lethality. Administration of recombinant IL-10 at 20 or 4 h before challenge, but not at later times, resulted in decreased tumor necrosis factor alpha levels and improved survival. IL-10 could be potentially useful for the treatment of GBS sepsis.